Intraoperative Myelography in Cervical Multilevel Stenosis Using 3D Rotational Fluoroscopy: Assessment of Feasibility and Image Quality. (2nd August 2015) - Westermaier, Thomas; Koehler, Stefan; Linsenmann, Thomas; Kiderlen, Michael; Pakos, Paul; Ernestus, Ralf-Ingo
Abstract : Background . Intraoperative myelography has been reported for decompression control in multilevel lumbar disease. Cervical myelography is technically more challenging. Modern 3D fluoroscopy may provide a new opportunity supplying multiplanar images. This study was performed to determine the feasibility and image quality of intraoperative cervical myelography using a 3D fluoroscope. Methods . The series included 9 patients with multilevel cervical stenosis. After decompression, 10 mL of water-soluble contrast agent was administered via a lumbar drainage and the operating table was tilted. Thereafter, a 3D fluoroscopy scan (O-Arm) was performed and visually evaluated. Findings . The quality of multiplanar images was sufficient to supply information about the presence of residual stenosis. After instrumentation, metal artifacts lowered image quality. In 3 cases, decompression was continued because myelography depicted residual stenosis. In one case, anterior corpectomy was not completed because myelography showed sufficient decompression after 2-level discectomy. Interpretation . Intraoperative myelography using 3D rotational fluoroscopy is useful for the control of surgical decompression in multilevel spinal stenosis providing images comparable to postmyelographic CT. The long duration of contrast delivery into the cervical spine may be solved by preoperative contrast administration. The method is susceptible to metal artifacts and, therefore, should be applied before metal implants are placed.